Dynamic viscosity of binary and ternary mixtures containing poly(ethylene glycol), potassium phosphate, and water - Telis-Romero, J.; Coimbra, JSR; Gabas, A. L.; Rojas, EEG; Minim, L. A.; Telis, VRN (Amer Chemical Soc, 2004)
Dynamic viscosity of binary mixtures of poly(ethylene glycol) molar mass 1500 da + water, potassium phosphate + water, and ternary mixtures of poly(ethylene glycol) molar mass 1500 da + potassium phosphate + water were determined at 303.15 K Binary and ternary mixture viscosities showed a direct logarithm-type relation with the increase of poly(ethylene glycol) and potassium phosphate contents. The models used for viscosity correlation gave a good fit to the experimental data.